The impact of efficiency on discretionary loans/finance loss provision: a comparative study of Islamic and conventional banks - Shawtari, Fekri Ali; Saiti, Buerhan; Abdul Razak, Shaikh Hamzah; Ariff, Mohamed (Elsevier, 2015)
The paper investigates whether there is a significance difference between the practices of discretionary loan/finance loss provisions between Islamic and conventional banks. Same time, the paper tests whether the efficiency may influence the behaviour of discretionary loans/finance loss provisions, taken into consideration other micro and macro variables. The study utilizes panel data runs over 1996e2011 with unbalanced observations for 16 banks, of which 4 Islamic banks. In order to achieve research objectives, the two-stage approach is adopted to examine the factors that may influence the behaviour of discretionary loan/finance loss provisions with specific emphasize on the efficiency. Furthermore, efficiency scores are estimated using Data Envelopment Windows Analysis. The findings of the research show that Islamic banks employ the discretionary loans/finance loss provisions to manage their earnings. However, the magnitude of discretion of accruals is significantly lower than conventional banks with exception for foreign banks which have reported lower discretionary loans/finance loss provisions than Islamic banks. Moreover, the analysis showed that efficiency affects the overall discretionary loans/finance loss provision positively, although this impact is shaped differently for Islamic and conventional banks.